HUJAN ASAM PADA BEBERAPA PENGGUNAAN LAHAN DI KABUPATEN DAN KOTA BOGOR (Acid Rain on Several Landuses in Bogor Regency and City) - R. Puripuspita Sari; Siti Badriyah Rushayati; Rachmad Hermawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Acid rain is caused by increasing air pollution. The emission of sulphur dioxide and nitrogen dioxide from fossil fuel combustion into the atmosphere, which is followed by a chemical transformation (hydrolysis) into sulphuric and nitric acid, causes acid rain. The study was conducted on four (4) locations with different landuses. The lowest pH of rainfall was on industrial area, whereas the highest pH of rainfall was on vegetation area. pH of rainfall in beginning of rainy season was lower than pH of rainfall in middle of rainy season.Keyword : Acid rain, pH, landuse, rainfal